The Influence of Work Communication and Work Discipline on Employee Performance at PT. Asahi Denso - Puspasari, Dewi; Dewi, Kisthi Hanila; Desan, Henriawan (Westscience Press, 2024)
Work communication is the main door for the flow of all ideas, ideas, problems and can even lead to innovation in work efficiency. Then work discipline is an important element in the world of work to maintain stability or a conducive work atmosphere. These two variables certainly have a role in maintaining employee performance in the company. This research method uses quantitative survey research with variables of work communication, work discipline and employee performance. The research location is at PT Asahi Denso Indonesia. Data analysis uses regression testing on variables. The results of research on work communication and work discipline have a significant simultaneous effect on employee performance. Furthermore, work communication has no effect on employee performance, while work discipline actually has a big effect on employee performance.